The last secret of the temple - Sussman, Paul
Joining forces with Israeli cop Arieh Ben-Roi, Egyptian detective Yusuf Khalifa investigates the discovery of a body at an isolated archaeological site, a death he connects with a murdered Israeli, which ultimately leads to an enigma dating back to 70 A.D.